Standardization Parameters for Herbal Formulation, Avipattikar Churnam - Dixit, Vihangesh Kumar; Irchhaiya, Raghuveer; Gupta, Rishikesh; Singh, Nandlal; Arjariya, Amita (Journal of Drug Delivery and Therapeutics, 2019)
Herbal formulations are being used by human society from a very long period of time. To ensure quality of the herbal formulation, a number of standardization parameters are set. Although there are large number of Ayurvedic formulations, standards of quality are yet to be laid for many of them. Avipattikar Churna is one of the important herbal formulation used for stomach diseases like dyspepsia, gastritis, hyper acidity, loss of appetite and stomach burning sensation. In this work, a standardization of herbal formulations of avipattikar churna is reported in terms of organoleptic evaluation of ingredients with rasayana formulation, loss of drying analysis, foreign matter, phytochemical screening, evaluation of ash value, extractive value and rheological evaluation.